2000
DOI: 10.1002/1098-1004(200008)16:2<166::aid-humu9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening the 3? region of the polycystic kidney disease 1 (PKD1) gene in 41 Bulgarian and Australian kindreds reveals a prevalence of protein truncating mutations

Abstract: Screening for disease‐causing mutations in the unique region of the polycystic kidney disease 1 (PKD1) gene was performed in 41 unrelated individuals with autosomal dominant polycystic kidney disease. Exons 34‐41 and 43‐46 were assayed using PCR amplification and SSCP analysis followed by direct sequencing of amplicons presenting variant SSCP patterns. We have identified seven disease‐causing mutations of which five are novel [c.10634‐10656del; c.11587delG; IVS37–10C>A; c.11669‐11674del; c.13069‐13070ins39] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These variants as well as two others were predicted to result in improper splicing by both the ASSA and SSPNN programs (Supp Table 2). In addition, IVS37-10C>A (JHU 604), was previously reported to segregate with ADPKD in a European family [38]. Although these intronic variants are likely to represent splicing mutations, aberrant splicing could not be confirmed at the RNA level using this DNA based assay.…”
Section: Class II Testsmentioning
confidence: 87%
“…These variants as well as two others were predicted to result in improper splicing by both the ASSA and SSPNN programs (Supp Table 2). In addition, IVS37-10C>A (JHU 604), was previously reported to segregate with ADPKD in a European family [38]. Although these intronic variants are likely to represent splicing mutations, aberrant splicing could not be confirmed at the RNA level using this DNA based assay.…”
Section: Class II Testsmentioning
confidence: 87%
“…Interpretation of a 39-bp insertion in the PKD1 gene [Bogdanova et al, 2000], a 29-bp insertion in the ATM gene [Vorechovsky et al, 1996], and a 27-bp insertion in the TCF1 gene [Godart et al, 2000]. Identical nucleotides between the inserted sequences and their wild-type 5 0 £anking sequences are shaded or in bold.…”
Section: Normal Replicationmentioning
confidence: 99%
“…Previous reports suggested that new mutations of the PKD1 gene occur at a significant rate (Peral et al 1997;Rossetti et al 2001). Approximately 80% of the mutations in the 3ЈPKD1 unique region (exons 34-46) were predicted to truncate the protein, and 37% of mutations in the 5Јpart of the gene were missense mutations (Bogdanova et al 2000). More mutations were found in exons 15, 23, 25, and 44, but these exons are not considered hot spots for mutations.…”
Section: Introductionmentioning
confidence: 99%